Tooth loss and associated factors during periodontal maintenance care in young adults with Grade C Periodontitis at a tertiary care center in Kathmandu, Nepal - Khushboo Goel; Sirjana Dahal (PLoS ONE, 2026)
Background This study aimed to evaluate tooth loss attributable to periodontal disease during periodontal maintenance care (PMC) in young adults with Grade C Periodontitis and to identify factors associated with tooth loss. Methods A total of 63 patients (mean age: 29.49 ± 4.65 years) were included. All patients received non‑surgical periodontal therapy using a comprehensive full‑mouth disinfection protocol with adjunctive systemic antibiotics as part of active periodontal therapy (APT), delivered through an individualized treatment approach. Clinical assessments were performed after completion of APT (T1) and during PMC, T2. Multivariable Firth-penalized Cox proportional hazards regression was applied to identify factors associated with time to tooth loss. Results A total of 1,709 teeth (1,228 non-molars, 481 molars) were analyzed. Over a mean follow‑up period of 60 ± 2 months, 15 teeth were lost, corresponding to an overall tooth loss rate of 0.88% (0.048 teeth/patient/year). Bone loss <60%, Molar‑Incisor Grade C Periodontitis, and adherence to PMC were associated with greater tooth retention. The overall regression model was statistically significant (likelihood ratio test p = 0.0016). Bone loss exceeding 60% was associated with a significantly increased hazard of tooth loss (HR: 14.83; 95% CI: 1.98–1896.79; p = 0.003), whereas compliant patients with PMC showed a significant protective association (HR: 0.29; 95% CI: 0.10–0.79; p = 0.016). Conclusion Tooth loss during PMC was minimal over 5 years. Severe periodontal bone loss and non‑compliance with maintenance care were associated with increased tooth‑loss risk. Long‑term retention of most teeth appears achievable through conservative periodontal management in young adults with Grade C Periodontitis.